High-Level Macrolide Resistance Due to the Mega Element [mef(E)/mel] in Streptococcus pneumoniae - Schroeder, Max R.; Lohsen, Sarah; Chancey, Scott T.; Stephens, David S. (Frontiers in Microbiology, 2019)
Transferable genetic elements conferring macrolide resistance in Streptococcus pneumoniae can encode the efflux pump and ribosomal protection protein, mef(E)/mel, in an operon of the macrolide efflux genetic assembly (Mega) element- or induce ribosomal methylation through a methyltransferase encoded by erm(B). During the past 30 years, strains that contain Mega or erm(B) or both elements on Tn2010 and other Tn916-like composite mobile genetic elements have emerged and expanded globally. In this study, we identify and define pneumococcal isolates with unusually high-level macrolide resistance (MICs >16 µg/ml) due to the presence of the Mega element (mef(E)/mel) alone. High-level resistance due to mef(E)/mel was associated with at least two specific genomic insertions of the Mega element, designated Mega-2.IVa and Mega-2.IVc. Genome analyses revealed that these strains do not possess erm(B) or known ribosomal mutations. Deletion of mef(E)/mel in these isolates eliminated macrolide resistance. We also found that Mef(E) and Mel of Tn2010-containing pneumococci were functional but the high-level of macrolide resistance was due to Erm(B). Using in vitro competition experiments in the presence of macrolides, high-level macrolide-resistant S. pneumoniae conferred by either Mega-2.IVa or erm(B), had a growth fitness advantage over the lower-level, mef(E)/mel-mediated macrolide-resistant S. pneumoniae phenotypes. These data indicate the ability of S. pneumoniae to generate high-level macrolide resistance by macrolide efflux/ribosomal protection (Mef(E)/Mel) and that high-level resistance regardless of mechanism provides a fitness advantage in the presence of macrolides.